Analysis of the distribution of land resources within the village of Bazaryanka Tuzlivska rural community Belgorod-Dnistrovsky district Odesa region by types of designated use - Tolmachova, A.; Danilova, N.; Kostiukievych, T.; Zhygailo, T.; Zhygailo, O. (Land Management, Cadastre and Land Monitoring, 2025)
Land is one of the main resources of the state, and effective land management affects the development of both the country as a whole and its individual territories. An important aspect of this process is the optimization of land use, which contributes to their rational distribution, increased productivity and balanced development of territories. The study of the division of land into categories, determination of their intended purpose and establishment of their form of ownership is of constant relevance in the field of land law. Not only the efficiency of land use, but also compliance with legal regulations, environmental safety and rational land use depend on the correct classification of land.The structure of the land fund of Bazaryanka village is dominated by agricultural land, with a total area of 814,40 ha. They are distributed as follows: 511,78 ha are arable land, 34,52 ha are pastures, and 268,10 ha are allocated for perennial plantations. Non-agricultural land occupies a relatively smaller share of 36,04 ha, which includes land under farm roads and runs (18,74 ha), shelterbelts (15,52 ha), and farm buildings and yards (1,78 ha). An analysis of land resources was carried out, which allowed to determine their distribution by ownership, among which the largest area is occupied by private land (823,37 ha). Keywords: designated purpose, land resources, agricultural land, forms of ownership.
Keywords: designated purpose; land resources; agricultural land; forms of ownership